Self-Efficacy And Continuous Professional Development: Challenges For Young Counselors In Dealing With Gen Z - Putri Natasya; Asbi; Restiana Syahfitri; Winda Muliani (Indonesian Journal of Communication and Social, 2026)
Generation Z, known as digital natives, brings new dynamics to the counseling landscape. Young counselors face unique challenges in understanding the characteristics of Gen Z, who are prone to mental health issues such as anxiety and stress, and expect flexible, technology-based services. This article examines the role of self-efficacy and continuous professional development as essential foundations for young counselors to address these challenges. Strong self-efficacy enables counselors to believe in their ability to provide effective services, while continuous professional development ensures the relevance of counselors' competencies with changing times. Through a literature review, this article discusses the characteristics of Gen Z, the challenges faced by young counselors, the importance of self-efficacy, and implementable strategies for continuous professional development. The aim is to provide guidance for young counselors to deliver relevant and effective guidance and counseling services for Generation Z.